Sistem Akuifer dan Potensi Airtanah Daerah Aliran Sungai (DAS) Opak - Setyawan Purnama; Suyono Suyono; Budi Sulaswono (Forum Geografi, 2007)
Opak River Basin is an area with high concentration of settlement. Generally, the settlement use groundwater as a water source. Variation of groundwater condition cause differentiation of water usage in some regions. There are two objectives of this research. First, to determine aquifer system in the research area and second, to calculate the groundwater potential in each aquifer system. To achieve these objectives, aquifer system is determined base on its geology and geomorphology, whereas groundwater potency is calculated by static and dynamic approach. As a result, show that the aquifer system in Opak River Basin can be distinguished into seven aquifer system. There are The Upper Merapi Aquifer System, The Middle Merapi Aquifer System, The Lower Merapi Aquifer System, Baturagung Range Aquifer System, The Aquifer System of Baturagung Range Foot Slope, Sentolo Hill Aquifer System and Sanddune Aquifer System. Among the seventh aquifer system, The Middle Merapi Aquifer System, The Lower Merapi Aquifer System and The Sanddune Aquifer System have high productivity. Sentolo Hill Aquifer System and The Aquifer System of Baturagung Range Foot Slope Aquifer have low productivity, whereas The Baturagung Range is categorized as non akuifer.